Prevalence of celiac disease in irritable bowel syndrome patients: A single centre experience from a large teaching hospital of Lahore, Pakistan (Journal of Fatima Jinnah Medical University, 2021)
Background: Many studies have been conducted worldwide to evaluate the proportion of patients with Celiac disease (CD) in persons presenting with Irritable Bowel Syndrome (IBS), showing a positive association between the two diseases. However, reports from Pakistan remain scanty. This study aims to find out the prevalence of CD in patients presenting with IBS and to establish the correlation of both diseases.Patients and methods: It was a descriptive cross-sectional study conducted at Combined Military Hospital, Lahore (CMHL) from January 2018 till March 2019. Consecutive, nonprobability sampling was used to include 210 patients of both genders with the age range of 15-65 years fulfilling ROME IV criteria and were not previously diagnosed as CD or CKD or CLD. Demographic data was noted. Serum Anti tTG levels and Duodenal Biopsy from the second part was assessed to diagnose CD. CD was labeled if the disease was present on both serological and Histopathological reports. Data were analyzed by using SPSS version 20. Descriptive statistics were calculated and a Chi-square test was used to compare the outcome variables with P-value < 0.05 as significant.Results: Of 210 enrolled patients, 113 (53, 8%) were male and 97 (46.2%) were female. The mean age of the patients was 28.40 ± 5.06 years. Eight patients (3.8%) were positive for Anti tTg and on histopathological findings suggestive of CD. Seven of 8 were less than 35 years old. Out of 8 positive patients, 6 (75%) were females. However, the p-value was found to be insignificant for age (0.549) and gender (0.096). On stratification with respect to duration of IBS, all 8 patients diagnosed with celiac disease were having symptoms of IBS for less than 12 months (100%) which was significant statistically (7.1% vs 0.0%; p=0.007).Conclusion: The frequency of CD was 3.8% among IBS patients. Considering this percentage of CD in IBS patients s, a high index of suspicion for CD in IBS patients is required,
Keywords: Irritable Bowel Syndrome (IBS); Celiac disease (CD); Serum anti tTG; Duodenal biopsy